Reliable information rate of signal‐time coding for half‐duplex additive white Gaussian noise relay networks. Issue 1 (28th December 2011) - Xiong, Ke; Fan, Pingyi; Qiu, Zhengding; Letaief, Khaled Ben
ABSTRACT Signal‐time coding (STC) is a newly proposed transmission scheme for half‐duplex relay networks, which is able to achieve higher information flow rate by combining the traditional encoding/modulation mode in the signal domain with the signal pulse phase modulation in the time domain. However, most of the results for STC are only obtained under the ideal assumptions that the signal detections at physical layer are perfect and there are still a lot of fundamental problems to be explored. This paper considers the implementing issues of STC at physical layer in additive white Gaussian noise relay networks. Firstly, a performance evaluation criterion, the reliable information per symbol (RIPS), is proposed to characterize the performance of STC in noisy wireless networks. Secondly, a new construction scheme based on route ID for the codeword of STC is presented, and some structural properties of the codeword of STC are investigated. Thirdly, the error probabilities of STC in both the signal domain and the time domain are discussed. Furthermore, two implementing schemes, that is, the energy detection based STC (ED‐STC) and the symbol detection based STC (SD‐STC), are proposed, and their performance bounds in terms of RIPS are discussed. Numerical analyses show that both ED‐STC and SD‐STC outperform traditional transmission methods in terms of effective information rate even under some practical conditions. Copyright © 2011 John Wiley & Sons, Ltd.